Anti-Avoidance Rules di Indonesia Pasca Amandemen UU Pajak Penghasilan - Adrianto Dwi Nugroho (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2009)
The fourth amendment to the Indonesian Income Tax Act (UU PPh) has inserted three new provisions encountering three newly-identified tax avoidance schemes. However, the previous regulations in respect of thin capitalization, CFC and interest stripping were not carefully be given attention and be made in conformity with their newest developments. As an illustration, the term “company” has never been defined in the Act. Instead, the Act introduces the same term in the conduit company rules. Another example involves the CFC rule which does not put additional provisions to define “control”. Another interesting development is the regulation of the International-hiring out of labor which instead of making it in conformity with the OECD MC, the rule empowers the country to increase the taxable income of an employee in respect of employment excercised abroad. This article attempts to demonstrate how the Indonesian anti-avoidance rules work out and prove how taxpayers may well, ironically, abuse those rules.